Identification and RNAi-Based Functional Analysis of Four Chitin Deacetylase Genes in Sogatella furcifera (Hemiptera: Delphacidae). Issue 4 (1st August 2021) - Yang, Xi-Bin; Zhou, Cao; Gong, Ming-Fu; Yang, Hong; Long, Gui-Yun; Jin, Dao-Chao
Abstract: Chitin deacetylases (CDAs) are chitin-degrading enzymes that play a key role in insect molting. In this study, we identified and characterized four full-length cDNAs of CDAs from Sogatella furcifera (Horváth). Developmental expression showed that SfCDA1 and SfCDA2 were expressed at all nymph developmental stages, SfCDA3 and SfCDA4 were mainly expressed in the third-instar to fifth-instar nymph stages, whereas tissue-specific analyses indicated that four CDA genes were mainly high expressed in the integument and head during the fifth-instar nymph. RNA interference (RNAi) results revealed that SfCDA1, SfCDA2, and SfCDA4 are associated with molting defect and high mortality with nymph–adult molting. Furthermore, transcripts of chitin synthase 1 variants ( SfCHS1, SfCHS1a, and SfCHS1b ) were significantly downregulated and causing significant changes in the expression levels of trehalases ( TRE1 and TRE2 ) in the SfCDA1, SfCDA2, and SfCDA4 dsRNA treatment groups. By contrast, no significant phenotypic characteristics were observed after ds SfCDA3 injection. Taken together, our results suggest that SfCDA1, SfCDA2, and SfCDA4 play a vital role in nymph-adult transition, and these genes could regulate chitin biosynthesis expression levels.